Cutaneous metastases of non‐cutaneous neuroendocrine neoplasms: A histopathologic review of 15 cases. (15th August 2022) - Hobbs, Misty M.; Snow, Justin T.; Shachner, Tracy R.; Sokumbi, Olayemi
Abstract: Background: Cutaneous metastases from non‐cutaneous neuroendocrine neoplasms are rare; however, distinction from primary neuroendocrine carcinomas of the skin (Merkel cell carcinoma) guides clinical management. Methods: We performed a retrospective review from September 1, 2010 to September 30, 2020 of the histopathologic, immunohistochemical, and clinical characteristics of metastatic neuroendocrine neoplasms to the skin from non‐cutaneous primaries. Results: Fourteen patients were identified for the study (nine males and five females; mean age of 59.5 years). Fifteen skin specimens from 14 patients were available for review. At the time of skin biopsy, a known non‐cutaneous neuroendocrine neoplasm was present in 50% of patients. Primary sites of neuroendocrine carcinoma included lung ( n  = 5), terminal ileum ( n  = 2), and one each from prostate, breast, rectum, uterus, esophagus, and sinus, with one unknown (suspected bladder malignancy). Eleven of fourteen patients are dead of disease; one was lost to follow‐up. All 15 specimens showed subcutaneous/deep dermal involvement with six involving the papillary dermis and one involving the epidermis. The tumors ranged from well to poorly differentiated. Two of fifteen specimens showed focal CK20 positivity (one metastatic uterine small cell carcinoma and one metastatic ileal carcinoid). TTF‐1 was performed in 13 specimens and was positive in six, of which two were of non‐pulmonary origin. Conclusions: While immunohistochemical stains, in particular CK20, CK7, and TTF‐1, are integral in the workup of confirming the origin of neuroendocrine tumors found in the skin, results vary and are often non‐specific for a single primary site. Therefore, complete radiologic imaging as well as clinical correlation should be recommended to further aid in the identification of a non‐cutaneous primary neoplasm.